Advancement of the Greenhouse with the Usage of a Wireless Sensor Network with Optimised Routing - Saxena, Tanu; Singh, Narendra Pal (International Journal of Computer Sciences and Engineering, 2022)
Due to the growing demand for crop output, quality, and the usage of high-quality greenhouses, modern greenhouses are becoming larger and more complex in their monitoring and control systems. The rise in greenhouse size has increased the necessity for real-time monitoring of certain parameters. This has added complexity to their management and maintenance. The purpose of this paper is to describe a wireless sensor network-based system for monitoring and controlling greenhouses. Because tiny nodes are utilised in WSN, they are spatially scattered, battery-powered, and energy- limited; as a result, nodes may die, resulting in communication failure. Thus, to address this shortcoming, we propose a routing protocol that balances resource usage across all sensor nodes, thereby extending the sensor node's lifetime. As a result, a potential greenhouse capable of measuring a variety of factors has been created.